2015
DOI: 10.1111/jeb.12752
|View full text |Cite
|
Sign up to set email alerts
|

Within‐species variation in long‐term trajectories of growth, fecundity and mortality in the Collembola Folsomia candida

Abstract: Senescence--the progressive deterioration of organisms with age--affects many traits of which survival and reproduction are the most commonly studied. Recent comparative studies have revealed a remarkable amount of variation in the patterns of ageing across the tree of life. This between-species diversity raises many questions about the evolution of senescence and of the shapes of the life-history age trajectories. Here, we study how the different components of the shapes of these life-history age trajectories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…TO also produces on average larger clutches than HA (Figure S4a), grows faster between 21 and 26°C and reaches slightly larger asymptotic lengths over the whole temperature range (Figure ). These observations confirm that HA has a slow life‐history strategy compared to TO (Mallard et al, ; Tully & Ferrière, ) which remains true under a broad temperature range. Interestingly, we show that the faster lineage also exhibits the stronger TSR response in population.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…TO also produces on average larger clutches than HA (Figure S4a), grows faster between 21 and 26°C and reaches slightly larger asymptotic lengths over the whole temperature range (Figure ). These observations confirm that HA has a slow life‐history strategy compared to TO (Mallard et al, ; Tully & Ferrière, ) which remains true under a broad temperature range. Interestingly, we show that the faster lineage also exhibits the stronger TSR response in population.…”
Section: Discussionsupporting
confidence: 82%
“…Briefly, we followed individuals from two clonal lineages (labelled TO and HA) either isolated or in populations at six different temperatures (6, 11, 16, 21, 26 and 29°C). These two lineages have two contrasted life‐history strategies along a slow (HA)–fast (TO) continuum (Mallard, Farina, & Tully, ; Tully & Ferrière, ) and may differ in their competitive abilities. In this species, the strength of competition is expected to increase with adult density because large individuals are known to monopolize food sources through interference competition (Le Bourlot, ; Le Bourlot, Tully, & Claessen, ) and with the rate of reproduction which reflects the resource requirements (Tully & Ferrière, ).…”
Section: Methodsmentioning
confidence: 99%
“…As a parthenogenetic species, multiple individuals sharing the same genotype can easily be bred in different environmental conditions. We worked with two distinct genetic clonal lineages (labelled respectively TO and HA) with contrasted ecological history and bio-demographic strategies (Tully, D'Haese, Richard, & Ferriere, 2006;Tully & Ferrière, 2008;Tully & Lambert, 2011;Mallard et al, 2015): at 21°C at low density, HA individuals have on average a lower reproductive potential and a lower basal mortality than TO individuals and they reach a higher body length. But the ecological natural conditions in which these lineages are adapted are not known.…”
Section: (I) the Collembola Folsomia Candida As A Model Organismmentioning
confidence: 99%
“…For subsequent analyses we further included the body length of each individual in the analysis to test for a size effect on individual movement probability. Since mean body length can vary substantially among clones (Mallard et al, 2015), we calculated for each treatment the corrected body lengths as the sum of the overall mean body length and the body length residuals computed here as the difference between individual lengths and mean length of their clone. This "corrected body length" was then used to study the effect of body length while controlling for differences among clones.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Earlier studies on several parthenogenetic lineages have uncovered substantial intra-specific genetic and morphological polymorphism (Chenon et al, 2000;Tully et al, 2006;Tully and Potapov, 2015). Intra-specific diversity is organised in two major evolutionary clades (Tully et al, 2006;Tully and Potapov, 2015), and life history studies have shown that two contrasted biodemographic strategies evolved along the divergence of these two clades (Tully and Ferriere, 2008;Tully, 2004;Tully and Lambert, 2011;Mallard et al, 2015). One clade has a high reproductive potential: when sufficient food is available, these springtails produce on average larger clutches than the ones from the other clade (Tully and Ferriere, 2008), but they have shorter mean lifespans than the less fecund clade and also reach a smaller adult body size (Tully and Ferriere, 2008;Tully and Lambert, 2011;Mallard et al, 2015).…”
Section: Introductionmentioning
confidence: 99%